Simulation of tomato growth, water and N dynamics using the EU-Rotate_N model in Mediterranean greenhouses with drip irrigation and fertigation - Soto Bravo, Freddy (2014)
tThe EU-Rotate N simulation model was evaluated with tomato grown in Mediterranean greenhousesto simulate (i) dry matter production (DMP), (ii) crop N uptake, (iii) marketable fresh yield, (iv) ETc,(v) drainage, (vi) NO3−leaching, and (vii) soil water and mineral N dynamics. Crops were grown withfrequent drip irrigation and fertigation, N was applied in all irrigations. Ten treatments were examinedin four years with differences in irrigation, applied N and soil mineral N at planting. Given that (a) EU-Rotate N default values are for open field crops and (b) that there are clear differences in management andgrowing conditions between greenhouse and open field tomato, it was necessary to calibrate relevantmodel parameters. Where N was not limiting, simulations of seasonal DMP and N uptake were veryaccurate with linear relationships between simulated and measured values having slopes of 1.0 andcoefficients of determination (R2) of 0.97 for DMP and of 0.95 for N uptake. Under N-limited conditions,simulated values of these parameters were underestimated by an average of 37%. Results for simulationsof marketable yield were similar. ETcwas very accurately simulated for all treatments. Simulation ofdrainage was acceptable for nine treatments with drainage values <60 mm, it was overestimated forone treatment with drainage >60 mm. Simulation of NO3−leaching was less accurate, on average, totalNO3−leaching was underestimated by 31%. There was generally good simulation of soil water dynamics.In 8 of 10 treatments, soil mineral N (0–60 cm depth) was accurately simulated. In two treatments, soilmineral N was substantially underestimated which appeared to be associated with inaccurate simulationof N mineralization under warm conditions. Comparison of simulations between three treatments withsubstantial differences in irrigation, N management and in soil mineral N at planting, demonstrated theusefulness of EU-Rotate N to examine the effects of crop management on drainage, NO3−leaching, and soilmineral N dynamics associated with tomato grown in greenhouse conditions. Following calibration, EU-Rotate N can be an effective tool for evaluating management practices and for demonstration purposes.